2007
DOI: 10.2353/ajpath.2007.070528
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress, Gene Expression, and Protein Changes Induced in the Human Placenta during Labor

Abstract: Malperfusion of the placenta has been implicated as a cause of oxidative stress in complications of human pregnancy, leading to release of proinflammatory cytokines and anti-angiogenic factors into the maternal circulation. Uterine contractions during labor are known to be associated with intermittent utero-placental perfusion. We therefore tested whether oxidative stress, proinflammatory cytokines, and angiogenic regulators were increased in placentas subjected to short (<5 hours) and long (>15 hours) labor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
206
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 270 publications
(214 citation statements)
references
References 61 publications
6
206
1
1
Order By: Relevance
“…We have observed the same distribution of oxidative stress in placentas from uncomplicated pregnancies following labour and vaginal delivery, while it is absent from those delivered by caesarean section (Fig. 4; Cindrova-Davies et al 2007).…”
Section: Dysregulation Of Placental Angiogenesis In Pathological Pregmentioning
confidence: 48%
“…We have observed the same distribution of oxidative stress in placentas from uncomplicated pregnancies following labour and vaginal delivery, while it is absent from those delivered by caesarean section (Fig. 4; Cindrova-Davies et al 2007).…”
Section: Dysregulation Of Placental Angiogenesis In Pathological Pregmentioning
confidence: 48%
“…Recently, it was shown that labor initiates oxidative stress which, depending on length and intensity, varies with the lowest degree of stress found in placental tissue from elective cesarean section [41]. As far as the gene profile is concerned, there apparently is no unanimous opinion [42].…”
Section: Discussionmentioning
confidence: 99%
“…Although preterm placentas would match the gestational age of the IUGR and PEϩIUGR placentas, they are commonly associated with pathological processes 54,55 and so there is considerable doubt as to whether they are truly normal. In addition, our previous results have shown that labor induces significant cellular stress within the placenta, 56 and nonlabored preterm healthy placentas delivered by elective caesarean section are almost impossible to obtain. On the other hand, we did not observe any correlation between gestational age and any of the data presented (Figure 1).…”
Section: Discussionmentioning
confidence: 99%